Analysis of Employee Constraints and Perceptions on the Implementation of E-Kinerja in Performance Assessment (A Case Study at The Baturetno Sub-District Office) - Vita Ariyana; Zandra Dwanita Widodo; Atik Lusia (ProBisnis : Jurnal Manajemen, 2026)
Employee performance assessment is an important part of increasing effectiveness and responsibility in the work of government employees. With the development of information technology, the government has begun to use the e-kinerja system as a way to assess employee performance in a bold manner. However, in its implementation there are still various problems that hinder it. This research aims to overcome existing obstacles and employee perceptions of the use of e-kinerja in performance appraisals at the Baturetno District Office. This research uses a qualitative approach by collecting data through observation and interviews. The results show that there are several obstacles such as inadequate networks, complicated systems, and differences in employee abilities in using applications. Research also finds that obstacles are not only technical, but also non-technical, where non-technical obstacles have more influence on the successful use of e-kinerja. Apart from that, according to the findings, employee perceptions vary greatly regarding the use of e-kinerja. This shows that the successful implementation of e-kinerja does not only depend on the quality of the system, but also on employee readiness and support from the organization.